Submission of the parts to the Belgien tribunals about the international agency agreements: comments about the judgement issued by the Audiencia Provincial de Barcelona on 21 December 2018 - Aguilar Grieder, Hilda (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
This study analyses an international jurisdiction problem which arises frecuently in the frame of international agency agreements.
Keywords: European Union; Private International Law; international jurisdiction; jurisdiction clauses; international agency agreements